Detoxification of Aflatoxin B(1) by Zygosaccharomyces rouxii with Solid State Fermentation in Peanut Meal - Zhou, Guanghui (Toxins (Basel), 2017)
Aflatoxins are highly carcinogenic, teratogenetic, and morbigenous secondary metabolites of Aspergillus flavus and A. parasiticus that can contaminate multiple staple foods, such as peanut, maize, and tree nuts. In this study, Zygosaccharomyces rouxii was screened out and identified from fermented soy paste—one kind of traditional Chinese food—to detoxify aflatoxin B(1) (AFB(1)) by aerobic solid state fermentation in peanut meal. The optimal degradation condition was chosen from single factor experiment, and the most effective detoxification rate was about 97%. As for liquid fermentation, we tested the binding ability of Z. rouxii, and the highest binding rate reached was 74.3% (nonviable cells of Z. rouxii) in phosphate-buffered saline (PBS). Moreover, the biotransformation of AFB(1) through fermentation of Z. rouxii in peanut meal was further verified by liquid chromatography/mass spectrometry (LC/MS). According to TIC scan, after fermentation by Z. rouxii, the AFB(1) in peanut meal was prominently degraded to the lowering peaks of AFB(1). Additionally, m/s statistics demonstrated that AFB(1) may be degraded to some new products whose structural properties may be different from AFB(1), or the degradation products may be dissolved in the aqueous phase rather than the organic phase. As far as we know, this is the first report indicating that the safe strain of Z. rouxii has the ability to detoxify AFB(1).